A Study on the Reporting Intention of Medical Incidents: A Nursing Perspective. (June 2018) - Chen, Li-Chin; Wang, Li-Hsiang; Redley, Bernice; Hsieh, Ya-Hui; Chu, Tsung-Lan; Han, Chin-Yen
Medical incidents threaten patients' lives and health, increase medical costs, and can lead to medical disputes. A high proportion of medical incidents are not reported. The aim of this study was to explore the factors influencing nurses' reporting of medical incidents. The cross-sectional survey design used a self-administered 47-item questionnaire to survey 835 nurses in three hospitals in Taiwan between January and December 2014. The intention among nurses to report medical incidents was high (3.86/5); nurses' intention to report medical incidents was positively correlated ( r = .34, p < .0001) with their attitude about reporting, awareness of reporting ( r = .37, p < .0001), and support from interested parties ( r = .12, p = .001), and was negatively correlated with positive incentives ( r = -.14, p < .0001) and negative incentives ( r = .29, p < .0001). Nurses' awareness and a supportive work environment affect nurses' willingness to voluntarily report medical incidents; hence, they are critical considerations as Taiwan moves toward systems of mandatory reporting.